Internet-based cognitive behavioural therapy (iCBT) for posttraumatic stress disorder versus waitlist control: study protocol for a randomised controlled trial. Issue 1 (December 2015) - Allen, Adrian; Newby, Jill; Smith, Jessica; Andrews, Gavin
Abstract Background This randomised controlled trial (RCT) with two parallel arms will evaluate the efficacy of an internet-delivered six-lesson 10-week cognitive behavioural therapy (iCBT) intervention for posttraumatic stress disorder (PTSD). It will also investigate the association between changes in PTSD symptoms, intolerance of uncertainty (IU) and emotion regulation. Methods/Design Patients with PTSD will be recruited via the research arm of a not-for-profit clinical and research unit in Australia and randomised to a treatment group or waitlist control group. The minimum sample size for each group (alpha 0.05, power 0.80 for ag of 0.47) was identified as 72, but 10 % more will be recruited to hedge against expected attrition. PTSD diagnosis will be determined using the PTSD module from the Mini International Neuropsychiatric Interview version 5.0.0. The PTSD Checklist – Civilian version (PCL-C) will be used to measure PTSD symptoms (the primary outcome measure), with the Intolerance of Uncertainty Scale 12-item version (IUS-12) and the Emotion Regulation Questionnaire (ERQ) used to measure intolerance of uncertainty and emotion regulation, respectively. The PCL-C will be administered to the treatment group before each lesson of the PTSD program and at 3-month follow-up. The IUS-12 and ERQ will be administered before lessons 1 and 4, at post-treatment and at 3-month follow-up. The waitlist control group will complete these measures at week 1, week 5 and week 11 of the waitlist period. PTSD program efficacy will be determined using intent-to-treat mixed models. Maintenance of gains will be assessed at 3-month follow-up. Mediation analyses using PROCESS will be used to examine the association between change in PTSD symptoms over treatment and change in each of IU and emotion regulation ability in separate analyses. Discussion The current RCT seeks to replicate previous efficacy findings of iCBT for PTSD in a formally assessed PTSD sample from the general population. Findings may point to future lines of enquiry for the role of IU and emotion regulation in the mechanism of PTSD symptom change during CBT. Trial registration Australian New Zealand Clinical Trials Registry:ACTRN12614001213639, registered 18 November 2014. This trial protocol is written in compliance with the Standard Protocol Items: Recommendations for Interventional Trials (SPIRIT) guidelines.